THE USE OF ECO ENZYME-BASED MUDBALLS IN REDUCING COD AND TSS POLLUTANTS IN POLLUTED RIVERS - Yonik Meilawati Yustiani; Fadjari Lucia Nugroho; Mimi Halimah; Monica Agustina; Azahra Siti Herbimaya; Gatut Sudarjanto; Ivan Aliyatul Humam (Universitas Trisakti, 2025)
Aim: This study aims to investigate the effectiveness of Eco Enzyme and EM1-based mudballs in improving river water quality by reducing COD and TSS. Methodology and Results: The study was conducted using an experimental method in the laboratory with four variations of mudballs, i.e. mudballs without additions, mudballs with Eco Enzyme, mudballs with effective microorganisms (EM1), and mudballs with a combination of Eco Enzyme and EM1. Artificial river water samples were made using glucose and kaolin solutions, and water quality was measured using the closed reflux method for COD, the gravimetric method for TSS, and pH measurements. Conclusion, significance and impact study: The results showed that all variations of mudballs were able to reduce COD and TSS values, but only the variation with a combination of Eco Enzyme and EM1 showed the most significant reduction in COD even though it had not reached the quality standard according to Government Regulation No. 22 of 2021. This variation was also effective in removing 100% TSS, and all variations managed to maintain the pH value within a safe range (6-9). The conclusion of this study is that the combination of Eco Enzyme and EM1 in mudballs provides the best results in improving river water quality, especially in TSS removal. However, further optimization is needed to remove COD to meet water quality standards.